Healthy Living and Social Justice: ADDRESSING THE CURRENT SYNDEMIC IN UNDERSERVED COMMUNITIES. Issue 3 (May 2021) - Arena, Ross; Laddu, Deepika; Severin, Richard; Hall, Grenita; Bond, Samantha
Abstract : Social Justice asserts all individuals are entitled to equal rights and opportunities, including the right to a healthy life and access to high quality health care. Adoption of and long-term adherence to healthy living behaviors requires that everyone have opportunities to be physically active and have access to healthy food.